Editor's Choice – Effect of Carotid Interventions on Cognitive Function in Patients With Asymptomatic Carotid Stenosis: A Systematic Review. (November 2021) - Ancetti, Stefano; Paraskevas, Kosmas I.; Faggioli, Gianluca; Naylor, A. Ross
Abstract : Objective: To determine the effect of carotid endarterectomy (CEA) and carotid artery stenting (CAS) on early (baseline vs. maximum three months) and late (baseline vs. at least five months) cognitive function in patients with exclusively asymptomatic carotid stenoses (ACS). Method: Searches were conducted in PubMed/Medline, Embase, Scopus, and the Cochrane library. This systematic review includes 31 non-randomised studies. Results: Early post-operative period: In 24 CEA/CAS/CEA+CAS cohorts ( n = 2 059), two cohorts (representing 91/2 059, 4.4% of the overall study population) reported significant improvement in cognitive function, while one (28/2 059, 1%) reported significant decline. Three cohorts (250/2 059, 12.5% reported "mixed findings" where some cognitive scores significantly improved, and a similar proportion declined. The majority (nine cohorts; 1 086/2 059, 53%) reported no change. Seven cohorts (250/2 059, 12.1%) were mostly unchanged but one to two individual test scores improved, while two cohorts (347/2 059, 16.8%) were mostly unchanged with one to two individual test scores worse. Late post-operative period: In 21 cohorts ( n = 1 554), one (28/1 554, 1.8%) reported significantly worse cognitive function, one reported significant improvement (24/1 554, 1.5%), while a third (19/1 554, 1.2%) reported "mixed findings". The majority were unchanged (six cohorts; 1 073/1 554, 69%) or mostly unchanged, but with one to two cognitive tests showing significant improvement (11 cohorts; 386/1 554, 24.8%). Overall, there was a similar distribution of findings in small, medium, and large studies, in studies with controls vs. no controls, in studies comparing CEA vs. CAS, and in studies with shorter/longer late follow up. Conclusion: Notwithstanding accepted limitations regarding heterogeneity within non-randomised studies, CEA/CAS rarely improved overall late cognitive function in ACS patients (< 2%) and the risk of significant cognitive decline was equally low (< 2%). In the long term, the majority were either unchanged (69%) or mostly unchanged with one to two test scores improved (24.8%). Until new research identifies vulnerable ACS subgroups (e.g., impaired cerebral vascular reserve) or provides evidence that silent embolisation from ACS causes cognitive impairment, evidence supporting intervention in ACS patients to prevent/reverse cognitive decline is lacking.